Breast Cancer Prevention Education for Adolescents through Timun Mas Folklore-Based Comics at Sekolah Rendah Islam I Musleh, Melaka, Malaysia - Arumsari, Wahyuni; Restu Ayu Eka Pustika Dewi; Inderiyani; Choirunisa Nur Rarastiti (Society : Jurnal Pengabdian Masyarakat, 2026)
Breast cancer remains one of the leading global public health problems and continues to contribute significantly to morbidity and mortality among women worldwide. The increasing incidence of breast cancer in Southeast Asia highlights the importance of strengthening preventive education and health literacy among adolescents. This community service program aimed to improve adolescents’ awareness and understanding of early breast cancer prevention through the use of Timun Mas folklore-based educational comics at Sekolah Rendah Islam I Musleh. The program employed a participatory educational approach involving upper elementary school students aged 11–12 years old. Activities were conducted through four stages: preparation, educational intervention, participatory interactive activities, and evaluation. Educational sessions combined interactive counseling, comic reading, group discussions, educational games, and reflective activities. The educational comics integrated health messages regarding healthy lifestyles, body awareness, reproductive health literacy, and the use of herbal plants such as temulawak, moringa leaves, and lemon within culturally familiar folklore narratives. The results demonstrated high participant enthusiasm and active engagement throughout the activities. Participants showed strong interest in the visual storytelling approach, which facilitated better understanding of health messages compared to conventional lecture-based methods. Positive feedback from school representatives indicated that the comics were attractive, communicative, and appropriate for elementary school students, while also highlighting the novelty of the educational media within the school environment. Furthermore, the availability of multimedia facilities at the school provides opportunities for future development of digital interactive comics and augmented reality (AR)-based educational media. Overall, the program demonstrated that folklore-based comics can serve as innovative, culturally responsive, and engaging health promotion media for adolescent breast cancer prevention education.